Qualitative Analysis Of Dentists' Behavior In Completing Odontogram Forms In The Outpatient Department Of RSIGM Sultan Agung Semarang - Shafira Raudya Aidina; Chriswardani Suryawati; Farid Agushybana (Green Publisher Indonesia, 2024)
One important part in the implementation of providing health services to patients in hospitals is medical records. The purpose of this study was to determine the relationship between dentist behavior and odontogram completeness, to analyze odontogram filling behavior from the aspect of the relationship between performance expectations, business expectations, social influence, and facilitating conditions, to improve dentist behavior towards filling odontogram completeness, and analyzed the relationship between intervention and completeness of odontogram filling.The type of research used is a qualitative research method. In order to improve the completeness of filling out the odontogram in Electronic Medical Record, it is necessary to consider the various factors that have been identified in this study.